2010
DOI: 10.1097/sle.0b013e3181cdb749
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Management of Left Thoracoabdominal Stab Wounds: A Prospective Study

Abstract: Laparotomy was required in only 11.1% (4/36) of the cases with LTSWs and 30.8% (4/13) of the cases with diaphragmatic injury. Diagnostic and therapeutic laparoscopy was a sufficient and necessary surgical procedure in cases with a hemodynamically stable LTSW, when emergency surgery (laparotomy or thoracotomy) was not necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
1
11
1
2
Order By: Relevance
“…This approach is supported by a recent study that reported a high prevalence of diaphragmatic or intra-abdominal injuries in such patients, and demonstrated the possibility of laparoscopic repair during the same session [3] .…”
Section: Management Of Left Thoracoabdominal Stab Woundssupporting
confidence: 69%
See 1 more Smart Citation
“…This approach is supported by a recent study that reported a high prevalence of diaphragmatic or intra-abdominal injuries in such patients, and demonstrated the possibility of laparoscopic repair during the same session [3] .…”
Section: Management Of Left Thoracoabdominal Stab Woundssupporting
confidence: 69%
“…expiration. Injuries to the diaphragm can be expected in more than 30% of patients with penetrating trauma to the thoracoabdominal area [3] . The diagnosis may not be apparent immediately and is missed initially in more than a third of the patients [4] .…”
Section: Case Reportmentioning
confidence: 99%
“…[4,[6][7][8]17,21,24,25] Diaphragm injury rates have been reported in range of 10% to 50% in several studies that investigated left thoracoabdominal stab injuries using diagnostic laparoscopy. [1][2][3][4][5]8,22,26,27] In the present study, diaphragm injury rate was 23.5% in all patients and 22.1% in patients who underwent diagnostic laparoscopy. Early diagnosis of diaphragm injuries in left thoracoabdominal stab injuries is challenging based on physical examination, chest X-ray, ultrasonography, and tomography.…”
Section: Discussionmentioning
confidence: 76%
“…Diyafragma yaralanmalarında laparoskopi gibi video yardımlı torakoskopi de tanı ve tedavide başarıyla kullanılmaktadır. [19,20] Akut yaralanmada diyafragma bütünlüğü bozulmadıysa non-absorbabl (0 veya 1 numara) sütür kullanılmalıdır. Ancak geniş defekt veya kronik olguda defekti güçlendirmek için prostetik meş ile desteklenmelidir.…”
Section: Discussionunclassified